Konsep Tata Ruang Goa Gajah dan Kolam Patirthan Berdasarkan Arsitektur Tradisional Bali - Ni Kadek Novera Litasaniadhari; Rochtri Agung Bawono; Ida Bagus Sapta Jaya (Syntax Corporation Indonesia, 2024)
The aim is to find out the application of the spatial layout of Goa Gajah and the Patirthan pond based on traditional Balinese architecture and to find out the relationship between Goa Gajah and the Patirthan pond reflected in the function of the building. The research method is qualitative with inductive reasoning. Data collection was carried out using literature studies, observations, interviews and documentation studies. The collected data was processed using spatial character analysis, contextual analysis and qualitative analysis supported by spatial theory of traditional Balinese architecture and architectural function theory. The results of the research concluded that Goa Gajah and the Patirthan pond were identified as being based on traditional Balinese architectural spatial concepts, namely; Tri Hita Karana; Tri Angga and Tri Loka; and orientations. Analysis of the relationship between Goa Gajah and the Patirthan pond also implies a philosophical relationship between mountains and the sea. The activities at Goa Gajah and the Patirthan pond clarify the relationship between buildings, and represent the building as a social environment for ascetics.